2013
DOI: 10.1111/jam.12237
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human adenovirus removal by qPCR in an advanced water reclamation plant in Georgia, USA

Abstract: Aims: To assess human adenoviruses (HAdVs) removal in an advanced wastewater treatment facility and compare two parallel tertiary treatment methods for the removal of HAdVs. Methods and Results: Tangential flow ultrafiltration was used to concentrate the water samples, and HAdVs were precipitated by polyethylene glycol. HAdVs were detected only by TaqMan real-time PCR, and HAdV genotype was determined by DNA sequence. HAdVs were detected in 100% of primary clarification influent, secondary clarification efflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In a research of Liu et al (2013),HAdVs were detected in 100% of primary clarification influent, secondary clarification effluent and granular mediafiltration effluent samples but only in 31.2% of membrane filtration effluent and 41.7% of final effluent samples, respectively. The average HAdVs loads were significantly reduced along the treatments but HAdVs were still present in final effluent (mean log 10 removals of HAdV from primary clarifer influent to second clarification, granular media filtration, membrane filtration and final effluent were 3.0, 3.2, 5.2, and 5.1, respectively).…”
Section: By Tertiary Treatment (Postsecondary)mentioning
confidence: 97%
See 1 more Smart Citation
“…In a research of Liu et al (2013),HAdVs were detected in 100% of primary clarification influent, secondary clarification effluent and granular mediafiltration effluent samples but only in 31.2% of membrane filtration effluent and 41.7% of final effluent samples, respectively. The average HAdVs loads were significantly reduced along the treatments but HAdVs were still present in final effluent (mean log 10 removals of HAdV from primary clarifer influent to second clarification, granular media filtration, membrane filtration and final effluent were 3.0, 3.2, 5.2, and 5.1, respectively).…”
Section: By Tertiary Treatment (Postsecondary)mentioning
confidence: 97%
“…The average HAdVs loads were significantly reduced along the treatments but HAdVs were still present in final effluent (mean log 10 removals of HAdV from primary clarifer influent to second clarification, granular media filtration, membrane filtration and final effluent were 3.0, 3.2, 5.2, and 5.1, respectively). Comparison showed that membrane filtration was technically superior togranular mediafor the removal of HAdVs (Liu et al, 2013). Human adenoviruses were detected in 82-100% of wastewater samples in a treatment plant in Germany with median concentration of 6.8x10 3 gene copies/L.…”
Section: By Tertiary Treatment (Postsecondary)mentioning
confidence: 99%
“…Eleven indices were evaluated based on data from Health Effects. Two parallel tertiary treatment methods for the removal of human adenoviruses (HAdVs), membrane filtration and granular media, were evaluated (Liu, Herzegh, et al, 2013). The study determined that although membrane filtration was found to be technically superior to granular media for the removal of HAdVs, they were not completely removed by treatment with either technology, which suggests a potential public health risk from exposure to the treated wastewater.…”
mentioning
confidence: 99%
“…Sanitation Score adenovirus, and norovirus were the most common in water samples 26 . While this study examined many viruses to assess water quality, other studies have used only adenovirus presence to represent all viral content of in the water 27,28 . One study measured the adenovirus DNA found in wastewater after treatment, as a proxy for viral content in treated water sources and found that the virus was not entirely removed during treatment, although infectivity was not tested 27 .…”
Section: Distribution Of Sanitation Score By Householdsmentioning
confidence: 99%
“…While this study examined many viruses to assess water quality, other studies have used only adenovirus presence to represent all viral content of in the water 27,28 . One study measured the adenovirus DNA found in wastewater after treatment, as a proxy for viral content in treated water sources and found that the virus was not entirely removed during treatment, although infectivity was not tested 27 . One study tested water sources for E. coli, enterococci, and somatic colophage, and found that only E. coli presence was associated with diarrhea in a village in Ecuador, although this could have been due to testing limitations for enterococci and somatic colophage 13 .…”
Section: Distribution Of Sanitation Score By Householdsmentioning
confidence: 99%